PENGARUH DISIPLIN, LINGKUNGAN KERJA DAN PELATIHAN TERHADAP KINERJA DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING - Safan, Azian M.; Sari, Kartika; Djati , Leryza Audryna (Fakultas Ekonomi Universitas Djuanda, 2025)
This study aims to analyze the effect of work discipline, work environment, and training on employee performance with commitment as an intervening variable at the Kopdit Guru Kelubagolit Savings and Loan Cooperative Office, East Flores Regency. The research method used is a quantitative. Data were collected through questionnaires distributed to all employees using a saturated sample of 64 employees. The analysis used multiple linear regression. The stages of analysis included validity, reliability, classical assumptions, partial tests, and Sobel tests to examine the role of intervening variables. The results showed that work discipline and training did not have a significant effect on commitment, while the work environment had a significant effect on employee commitment. Work discipline and commitment had a significant effect on employee performance, while the work environment and training did not have a direct effect on performance. Further findings indicate that commitment does not mediate the influence of work discipline and work environment on performance, but commitment is able to mediate the influence of training on employee performance. These findings confirm that improving employee performance is more effectively achieved through strengthening work discipline and organizational commitment, as well as optimizing training that can build employee commitment.